2019
DOI: 10.1016/j.celrep.2019.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Mycobacterium tuberculosis Exploits Multiple Host Nitrogen Sources during Growth in Human Macrophages

Abstract: SummaryNitrogen metabolism of Mycobacterium tuberculosis (Mtb) is crucial for the survival of this important pathogen in its primary human host cell, the macrophage, but little is known about the source(s) and their assimilation within this intracellular niche. Here, we have developed 15N-flux spectral ratio analysis (15N-FSRA) to explore Mtb’s nitrogen metabolism; we demonstrate that intracellular Mtb has access to multiple amino acids in the macrophage, including glutamate, glutamine, aspartate, alanine, gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 79 publications
6
91
0
2
Order By: Relevance
“…Mutation in phosphoserine aminotransaminase, serC that converts pyruvate to serine has shown that serC is required for growth of bacteria in serine auxotrophy. Further, similar results were observed in Mtb THP‐1 macrophages where, growth of serC mutant was tremendously impaired compared to wild type and serine complemented bacteria 74 …”
Section: Enzymes Of Amino Acid Metabolism As Drug Targetssupporting
confidence: 77%
“…Mutation in phosphoserine aminotransaminase, serC that converts pyruvate to serine has shown that serC is required for growth of bacteria in serine auxotrophy. Further, similar results were observed in Mtb THP‐1 macrophages where, growth of serC mutant was tremendously impaired compared to wild type and serine complemented bacteria 74 …”
Section: Enzymes Of Amino Acid Metabolism As Drug Targetssupporting
confidence: 77%
“…Mtb is known to be able to acquire and assimilate multiple carbon sources from the host during infection (5, 6, 13, 19). This co-catabolism has been demonstrated to occur both in vitro and during intracellular growth (14).…”
Section: Discussionmentioning
confidence: 99%
“…Within a subset of these, isotopologue abundances for the fragment formed by cleavage of the C2–C3 bond in serine were also determined allowing comprehensive characterization of the isotopic incorporation into serine. Mass spectra of the derivatized amino acids were corrected for the natural abundance of all stable isotopes (4, 6).…”
Section: Methodsmentioning
confidence: 99%
“…The authors also suggested that greater emphasis should be placed on amino acids as sole carbon sources to better mimic physiologically relevant conditions found in the host. Borah et al used 15 N-flux spectral ratio analysis to demonstrate that M.tb in macrophages has access to multiple amino acids for nitrogen metabolism and identified serine as an amino acid not available to intracellular bacilli [95]. The proteinogenic amino acid serine that provides the nitrogen backbone for glycine and cysteine synthesis must be synthesized by intracellular M.tb, highlighting this pathway, and phosphoserine transaminase in particular, as a novel target for drug discovery.…”
Section: Target Identificationmentioning
confidence: 99%